Profil Kebugaran Jasmani Siswa Kelas IV, V, dan VI Di Sekolah Dasar Negeri Sendang 01 - Ashar, Fillah; Indarto, Pungki (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the level of physical fitness of students in grades IV, V, and VI at Sendang 01 State Elementary School, Bringin District, Semarang Regency. The study used a quantitative descriptive method, with a survey research design in the form of field tests. The instrument used is an instrument in the archipelago student fitness test with the guidelines in it, the data analysis technique used is descriptive analysis in the form of a percentage. The sample in this study were students in grades IV, V, and VI of Sendang 01 State Elementary School, Bringin District, Semarang Regency, namely 44 students, this is the use of total sampling techniques, where the overall population approach that is the object of research is included as a sample. Based on the results and analysis in this study, it was found that the average level of physical fitness of students in grades IV, V, and VI of Sendang 01 State Elementary School, Bringin District, Semarang Regency was at a value of 2.4409 which shows the overall category as 'Sufficient'. However, further descriptive statistical analysis revealed that a total of 3 students, covering approximately 6.82% of the total sample, showed a level of understanding that fell into the 'Poor' category and a total of 4 students or 9.09% of the total sample fell into the 'Good' category. This indicates that the level of physical fitness of students needs to be improved through various effective and influential methods. The conclusion is that the level of physical fitness is in the sufficient category. Keywords: Physical Fitness, Physical Education, Sports